2016
DOI: 10.1016/j.ultramic.2015.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Ion microscopy based on laser-cooled cesium atoms

Abstract: We demonstrate a prototype of a Focused Ion Beam machine based on the ionization of a lasercooled cesium beam adapted for imaging and modifying different surfaces in the few-tens nanometer range. Efficient atomic ionization is obtained by laser promoting ground-state atoms into a target excited Rydberg state, then field-ionizing them in an electric field gradient. The method allows obtaining ion currents up to 130 pA. Comparison with the standard direct photo-ionization of the atomic beam shows, in our conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 24 publications
(46 reference statements)
0
27
0
Order By: Relevance
“…Our current setup does not include components for beam shaping or steering, therefore it is not possible to determine a focus size. However, spot sizes of a few tens of nanometers and below have been demonstrated with laser cooled sources [22,27] and by adding an appropriate ion optical setup, we expect similar performance to be achievable with our source. The stochastic nature of the ionization process leads to an exponential decay of the emission time.…”
Section: Resultsmentioning
confidence: 55%
See 1 more Smart Citation
“…Our current setup does not include components for beam shaping or steering, therefore it is not possible to determine a focus size. However, spot sizes of a few tens of nanometers and below have been demonstrated with laser cooled sources [22,27] and by adding an appropriate ion optical setup, we expect similar performance to be achievable with our source. The stochastic nature of the ionization process leads to an exponential decay of the emission time.…”
Section: Resultsmentioning
confidence: 55%
“…Due to this large energy spread, ion beam applications typically require beam energies in the 10 keV range in order to ensure good focusing. Recently, a third type of ion source based on photoionization of laser-cooled atoms is gaining increasing attention [22][23][24]. Due to the low temperature, such a source can feature a high brightness comparable to a LMIS, however, at a much lower energy spread of less than 1 eV, which allows operation also at low beam energies of a few hundred electronvolts [17].…”
Section: Introductionmentioning
confidence: 99%
“…( 14, 166 and 167 ) are still under development, although very recently, imaging with a focused Cs + beam has been demonstrated with this type of source. 169 In an alternate approach, Knuffman et al 170 have constructed and demonstrated a cold atom beam ion source of Cs ions based on a somewhat different concept, with the goal of creating a high brightness source of heavy ions for milling and circuit edit applications (Fig. 24).…”
Section: Cold Atomic Beam Sourcesmentioning
confidence: 99%
“…Recently, two prototype ultracold cesium FIBs have been realized. Viteau et al constructed an ion microscope based on the field ionization of Rydberg-level promoted cesium atoms [5]. From the obtained resolution combined with simulations an ion beam brightness of 2.8 × 10 5 A/(m 2 sr eV) was estimated.…”
Section: Introductionmentioning
confidence: 99%